PROSES PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU SMP - Murtiningsih, Murtiningsih; Lian, Bukman (Graduate Program Magister Manajemen Pendidikan, 2017)
Decision is the beginning of an action. Decision making in an educational organization is directly related to the principal. The principal as a manager has an important role in making decisions quickly, accurately and effectively by using data and information for optimal educational environment performance. Decision making conducted by State Secondary School principals 13 Palembang already been running well, this could be seen from the process and stages done by the principal with the decision with the observation, data, planning and registry related to education at school. Then, conduct deliberation with teachers to take a policy, interpersonally approach teachers to organize events, give ideas, engage teachers in training, and supervise as supervisory activities. As outlined in teacherâ€™s work assessment, it is useful to improve the potential and performance of teachers, to improve the quality of teaching and learning achievement State Secondary School 13 PalembangÂ Keywords: Principal, Decision-Making, Teachersâ€™ Performance, State Secondary School 13